Determinan Harga Saham pada Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) - Erna Pratika Sari; Anita Wijayanti; Purnama Siddi (Universitas Batanghari Jambi, 2020)
Valuation of stock prices is very important to be carried out by shareholders because stocks is promising type of investment. Examining the effect of of PER, GPM, ROE and operating cash flow on stock prices in companies listed on the Jakarta Islamic Index (JII) in 2015-2018 are the objectives of this research. With secondary data used in this research. Population in the study used 16 companies listed on the Jakarta Islamic Index (JII) in 2015-2018. Sampling using a purposive sampling method and samples obtained by 8 companies. Analysis with multiple linear regression. PER and GPM do no affect stock prices, while ROE and operating cash flow affect stock prices are the results of the study.